Apolipoprotein E genotype and the association between C‐reactive protein and postoperative delirium: Importance of gene‐protein interactions. Issue 3 (4th January 2020) - Vasunilashorn, Sarinnapha M.; Ngo, Long H.; Inouye, Sharon K.; Fong, Tamara G.; Jones, Richard N.; Dillon, Simon T.; Libermann, Towia A.; O'Connor, Margaret; Arnold, Steven E.; Xie, Zhongcong; Marcantonio, Edward R.
Abstract: Introduction: Apolipoprotein E (APOE) status may modify the risk of postoperative delirium conferred by inflammation. Methods: We tested whether APOE modifies the established association between C‐reactive protein (CRP) and delirium incidence, severity, and duration in 553 noncardiac surgical patients aged 70 and older. High postoperative plasma CRP (≥234.12 mg/L) was defined by the highest sample‐based quartile. Delirium was determined using the Confusion Assessment Method and chart review, and severity was determined by the Confusion Assessment Method—Severity score. Results: APOE ε4 carrier prevalence was 19%, and postoperative delirium occurred in 24%. The relationship between CRP and delirium incidence, severity, and duration differed by ε4 status. Among ε4 carriers, there was a strong relationship between high CRP (vs. low CRP) and delirium incidence (relative risk [95% confidence interval], 3.0 [1.4–6.7]); however, no significant association was observed among non‐ε4 carriers (relative risk [95% CI], 1.2 [0.8–1.7]). Discussion: Our findings raise the possibility that APOE ε4 carrier status may modify the relationship between postoperative day 2 CRP levels and postoperative delirium.